Кодовое название - "Тихий": военные повести / П. П. Любомиров - Любомиров Петр Петрович (Удмуртия, 1984)
Экземпляры: ф. 19 (20240116) / Инвентарный номер: 8481 / Цена: 0.50 / Авт.знак: Л93 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)